Humour in British First World War Literature - Anderson, Emily. author. aut Link
IX, 235 p. 3 illus.
Keywords: This book explores how humorous depictions of the Great War helped to familiarise, domesticate and tame the conflict. In contrast to the well-known First World War literature that focuses on extraordinary emotional disruption and the extremes of war, this study shows other writers used humour to create a gentle, mild amusement, drawing on familiar, popular genres and forms used before 1914. Emily Anderson argues that this humorous literature helped to transform the war into quotidian experience. Based on little-known primary material uncovered through detailed archival research, the book focuses on works that, while written by celebrated authors, tend not to be placed in the canon of Great War literature. Each chapter examines key examples of literary texts, ranging from short stories and poetry, to theatre and periodicals. In doing so, the book investigates the complex political and social significance of this tame style of humour. Emily Anderson is Associate Lecturer in the School of English Literature, Language and Linguistics at Newcastle University, UK. Her research interests are in humour and whimsy in British literature, focusing on the late nineteenth and early twentieth centuries.